ISO 9001:2015 Certification Audit at PT. Halal Syariah Integrasi and Its Implications for Quality Management Systems - Wiwiet Prihatmadji; Kiagus Muhammad Faisal; Teddy Setiady; Bakri; Retno Widowati (International Publisher, 2024)
ISO 9001 certification audit process for PT. Halal Syariah Integration (PT.HSI) by Mutu Certification with findings in the form of twelve non-conformity findings, and seven opportunities for improvement. The implications of the results of the findings are in the form of nine main steps to improvement at PT. HSI, namely: 1. Business process that describes the interaction of each organizational function, 2. Socialization of Quality Policy can be accessed by interested parties and be programmed systematically, 3. Determines General Company Regulations which contain the authority, responsibilities, requirements and competencies, 4. Prepares standardization of the learning process at LPK and LSP which includes infrastructure standards, educational staff, curriculum and learning module, 5. Infodok Standard SOP ensure that all organizational functions are equipped with work processes procedures, 6. Each organizational function should monitor, measure, analyze, evaluate the achievement of SMART Quality Goal targets, take corrective steps, and prevent failed targets, 7. Carry out analysis and evaluation of the perceptions of customers satisfaction, 8. Carry out internal quality audits in accordance with ISO 19011:2018 rules, with audit topics in accordance with ISO 9001:2015 requirements that are relevant to the organization's functions , 9. Management Review Meetings are carried out in accordance with the requirements of ISO 9001:2015, and contain recommendations and verification from Top Management regarding the results of management review meetings.